Optimizing calf growth performance and nutrient digestibility with whey dangke-enriched green calf starter (fodder-based proteins) in Holstein Friesian - Renny Fatmyah Utamy; Ambo Ako; Hasbi Hasbi; Zyahrul Ramadan; Yasuyuki Ishii; Sri Gustina; Mohammad Mijanur Rahman; Muhammad Ihsan Andi Dagong; Nur Amaliah; Kannika Umpuch (Instituto de Investigaciones Agropecuarias (INIA), Ministerio de Agricultura, Chile, 2024)
Common calf starters often contain fish meal as a primary protein source; however, the strong odour of fish meal hinders calves from consuming the feed, necessitating alternative protein sources. Thus, the research aims to optimize calf growth performance and nutrient digestibility using whey dangke-enriched green calf starter (fodder-based proteins) in Holstein Friesian calves. Dangke is a local soft cheese from Enrekang District, South Sulawesi, Indonesia, prepared using fresh milk heated and mixed with the enzyme papain. The Holstein Friesian calves were distributed into a completely randomized design to assess the impact of two key factors: The type of concentrate feed (common feed, T0 vs. green calf starter, T1) and the level of enriched whey- dangke: 0% whey dangke + 5% water (W0); 2.5% whey dangke + 2.5% water (W1); and 5% whey dangke + 0% water from body weight (W2). The use of T1 significantly differed (P < 0.01) from T0 in crude protein (CP) digestibility, energy digestibility, and feed conversion ratio, and significantly differed (P < 0.05) in average daily weight gain (ADG). Additionally, whey dangke levels showed a highly significant effect (P < 0.01) on CP digestibility, energy digestibility, insulin-like growth factor 1 (IGF-1) hormone levels, and significantly differed (P < 0.05) in shoulder height and body length. The T1 promotes higher ADG (660 g d-1) than the T0 (420 g d-1). Whey dangke enrichment enhances CP digestibility and energy digestibility, increasing IGF-1 hormone levels from 56.06 ng mL-1 (W0) to 80.76 ng mL-1 (W2). Feeding calves, a combination of green and common calf starter with enriched whey dangke significantly boosts growth performance compared to a diet without enrichment.